Social Adjustment of the Hearing Impaired Students in Special Education Centers in Jordan and its Relationship to Age & Degree of Impairment - Ayman Mazahreh; Naji al-Saaidah; Omar Al-kharabsheh; Yaquob Al-Farah (My University, 2010)
This study aimed at detecting the level of social adjustment and its relationship to age and degree of the hearing-impaired student in Jordan. The sample of the study consisted of one hundred students from the special education centers for the hearing impaired who were selected randomly. The social adjustment scale for the hearing impaired was implemented on them. Results have shown that the social adjustment level of the hearing impaired was high. Furthermore, results have shown that there are differences of statistical significance in the social adjustment level attributed to the severity of the impairment in favour of simple hearing – impaired students are evident. But no significant differences were found due to student’s age.

هدفت الدراسة إلى تعرف مستوى التوافق الاجتماعي وعلاقته ببعض المتغيرات لدى الطلبة المُعاقين سمعياً في الأردن. وقد تكونت عينة الدراسة من (100) طالبٍ وطالبة من طلبة مراكز التربية الخاصة للمُعوّقين سمعيا، تم اختيارهم بالطريقة العشوائية البسيطة. وتم استخدام مقياس التوافق الاجتماعي للمُعاقين سمعياً. توصلت النتائج إلى أن مستوى التوافق الاجتماعي لدى الطلبة المُعاقين سمعياً في محافظة البلقاء مرتفع. لكن النتائج لم تكشف عن فروق ذات دلالة إحصائية في مستوى التوافق الاجتماعي تعزى لمتغير العمر. كما توصلت النتائج إلى وجود فروق ذات دلالة إحصائية في مستوى التوافق الاجتماعي تعزى لمتغير شدة الإعاقة ولصالح ذوي الإعاقة السمعية البسيطة.
التوافق الاجتماعي وعلاقته بالعمر وشدة الإعاقة لدى الطلبة المُعاقين سمعياً بمراكز التربية الخاصة في الأردن